## Answer :

so centroid =( [tex] \frac{x1+x2+x3}{3} [/tex] , [tex]\frac{y1+y2+y3}{3}[/tex] )

so here 2,3 and 2, -1 and centroid = 1,2/3

so [tex] \frac{2+2+x}{3}=1[/tex] ⇒ x = -1

and [tex]\frac{3-1+y}{3}=\frac{2}{3}[/tex] ⇒ y = 0

so other vertex = (-1 , 0)

**Answer:**

**Step-by-step explanation:**

so for a triangle with vertices (x1,y1);(x2,y2);(x3,y3)

so centroid =( \frac{x1+x2+x3}{3} , \frac{y1+y2+y3}{3} )

so here 2,3 and 2, -1 and centroid = 1,2/3

so \frac{2+2+x}{3}=1 ⇒ x = -1

and \frac{3-1+y}{3}=\frac{2}{3} ⇒ y = 0

so other vertex = (-1 , 0)